2011
DOI: 10.1002/dvdy.22737
|View full text |Cite
|
Sign up to set email alerts
|

Pokes, sunburn, and hot sauce: Drosophila as an emerging model for the biology of nociception

Abstract: The word “nociception” is derived from the Latin “nocere,” which means “to harm.” Nociception refers to the sensory perception of noxious stimuli that have the potential to cause tissue damage. Since the perception of such potentially harmful stimuli often results in behavioral escape responses, nociception provides a protective mechanism that allows an organism to avoid incipient (or further) damage to the tissue. It appears to be universal in metazoans as a variety of escape responses can be observed in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
113
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 88 publications
1
113
0
1
Order By: Relevance
“…Invertebrates, by virtue of their relatively small, well-understood nervous systems and/or easy-to-manipulate genomes, have a demonstrable role in elucidating the fundamental mechanisms mediating both normal function and functional disorders of the nervous system. Examples of the latter include studies of neurodegenerative disease, spinal muscular atrophy, addiction, pain, as well as seizures (Cymbalyuk et al 2002;Walters and Moroz 2009;Grice et al 2011;Parker et al 2011;Therisa and Desai 2011;Im and Galko 2012;Giachello et al 2013;Li and Le 2013;Scholz and Mustard 2013;Sovik and Barron 2013). Although there can be significant differences between vertebrates and invertebrates in terms of molecules that mediate nervous system function, even these differences can be an advantage.…”
Section: Discussionmentioning
confidence: 96%
“…Invertebrates, by virtue of their relatively small, well-understood nervous systems and/or easy-to-manipulate genomes, have a demonstrable role in elucidating the fundamental mechanisms mediating both normal function and functional disorders of the nervous system. Examples of the latter include studies of neurodegenerative disease, spinal muscular atrophy, addiction, pain, as well as seizures (Cymbalyuk et al 2002;Walters and Moroz 2009;Grice et al 2011;Parker et al 2011;Therisa and Desai 2011;Im and Galko 2012;Giachello et al 2013;Li and Le 2013;Scholz and Mustard 2013;Sovik and Barron 2013). Although there can be significant differences between vertebrates and invertebrates in terms of molecules that mediate nervous system function, even these differences can be an advantage.…”
Section: Discussionmentioning
confidence: 96%
“…The responses to all these specific sensory cues depend not only on the type of neuron, but also on the molecular machineries involved [12,14,16]. A new paper [17] aims at putting together these elements into a complete circuit controlling the rolling escape response that presumably evolved in fly larvae to escape from parasitoid wasp adversaries.…”
Section: Current Biologymentioning
confidence: 98%
“…In recent years, this intriguing locomotor response has been gradually dissected at the neuronal and molecular level using the growing number of tools available in the fly [1,2,[4][5][6][7]. These studies have shown that a specific class of dendritic arborization (da) neurons, also called multidendritic (Md) neurons [8][9][10][11][12] is necessary and sufficient for the rolling response [1,2]. The different classes of Md neurons tile the surface of the larval cuticle and play key roles in sensing distinct types of stimuli in the environment of the larva [13,14].…”
mentioning
confidence: 99%
“…Flies provide a sophisticated genetic toolkit and a simplified nervous system that allow for precise genetic and neuronal manipulation 1,2,3,4 to dissect the cellular and molecular bases of nociception 5,6,7 . Larvae are particularly useful for these analyses, given that behavioral assays for gentle touch 8,9,10 , noxious heat 11,12,13 and mechanical sensation of noxious stimuli 4,11 have already been established, and the transparent larval cuticle allows for live or fixed imaging of the epidermis and underlying sensory neurons.…”
Section: Introductionmentioning
confidence: 99%